Temperature independent refractive index measurement using a fiber Bragg grating on abrupt tapered tip. (May 2018) - Gomes, André D.; Silveira, Beatriz; Warren-Smith, Stephen C.; Becker, Martin; Rothhardt, Manfred; Frazão, Orlando
Highlights: Temperature independent refractive index sensing. Higher order modes can be excited and thus greater sensitivity is achieved. Minimum RI sensitivity is 60% higher than the maximum reported previously. Simultaneous measurement of refractive index and temperature is also analyzed. The sensor have applications where temperature fluctuations need to be considered. Abstract: A fiber Bragg grating was inscribed in an abrupt fiber taper using a femtosecond laser and phase-mask interferometer. The abrupt taper transition allows to excite a broad range of guided modes with different effective refractive indices that are reflected at different wavelengths according to Bragg's law. The multimode-Bragg reflection expands over 30 nm in the telecom-C-band. This corresponds to a mode-field overlap of up to 30% outside of the fiber, making the device suitable for evanescent field sensing. Refractive index and temperature measurements are performed for different reflection peaks. Temperature independent refractive index measurements are achieved by considering the difference between the wavelength shifts of two measured reflection peaks. A minimum refractive index sensitivity of 16 ± 1 nm/RIU was obtained in a low refractive index regime (1.3475–1.3720) with low influence of temperature (−0.32 ± 0.06 pm/°C). The cross sensitivity for this structure is 2.0 × 10 −5  RIU/°C. The potential for simultaneous measurement of refractive index and temperature is also studied.